Physical modeling of turbulence wind field for wind turbines - ICASP14; Li, Jie; Peng, Yongbo; Chen, Jianbing; Liu, Zenghui (My University, 2023)
Wind load is one of the most important dynamic excitations of wind turbine systems, reasonable description and simulation of turbulence wind field lays a significant foundation for the elaborative dynamic response analysis and reliability assessment of wind turbine systems. Currently, the turbulence wind field modeling methods of wind turbine are mainly based on the empirical power spectrum models, and the simulation of wind field time histories are realized through the mathematical summation of stochastic harmonic waves. However, these methods can not reflect the physical mechanism of the turbulence wind field because they ignore the continuity condition and the governing equation of turbulence. In this view, a physical modeling approach of turbulence wind field for wind turbine systems is proposed in this paper. The turbulence wind field is regarded as an isotropic homogenous field, and Taylorﾒs frozen hypothesis is used to convert the 4-D space-time field into the 3-D spatial field. Then, the wave number spectrum tensor of the isotropic homogenous turbulence field is determined based on the symmetry conditions and the continuity condition of the homogenous turbulence field. Thus, the 3-D turbulence wind field can be represented through the spectral decomposition theory. In order to circumvent the obstacle of high-dimensional random variables in the numerical simulation formula, the evolutionary phase model is introduced to represent the random phase angles with just 4 elementary random variables. Using the proposed physical model, a turbulence wind field of 5MW OC3-Hywind wind turbine is simulated, and the technique of Fast Fourier Transform (FFT) is adopted to enhance the efficiency of simulation. The numerical results reveal the effectiveness of the proposed approach in the simulation of isotropic homogenous turbulence wind field.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED